Clinico‐pathological comparison of patients with autopsy‐confirmed Alzheimer's disease, dementia with Lewy bodies, and mixed pathology - Atri Chatterjee; Veronica Hirsch‐Reinshagen; Syed Ali Moussavi; Blake Ducharme; Ian R. Mackenzie; Ging‐Yuek Robin Hsiung (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2021)
Abstract Introduction Patients with Alzheimer's disease (AD) and dementia with Lewy bodies (DLB) frequently demonstrate coexistent AD neuropathological change (ADNC) and Lewy body pathology (LBP) at autopsy. We investigated the effects of ADNC and LBP on the clinical presentation of these patients. Methods We retrospectively compared clinical and pathological features of patients with different severity of ADNC and LBP. We also compared the burden of medullary LBP between patients with and without autonomic dysfunction. Results Compared to pure ADNC, patients with AD/LBP have higher prevalence of DLB symptoms. Autonomic dysfunction strongly predicted the presence of LBP in patients with clinically diagnosed AD, but was not associated with increased LBP burden in the medulla. Severity of ADNC, but not LBP, was associated with cerebral atrophy. Discussion Clinical presentation of patients with AD/LBP differs from patients with pure ADNC or LBP. Autonomic dysfunction is a useful marker of otherwise unsuspected LBP.